Unlocking the potential of flavonoid biosynthesis through integrated metabolic engineering - Wang, Yuan; Chen, Jiahong; He, Genhe; Yin, Li; Liao, Yonghui (Frontiers in Plant Science, 2025)
Flavonoids are a diverse class of plant polyphenols with essential roles in development, defense, and environmental adaptation, as well as significant applications in medicine, nutrition, and cosmetics. However, their naturally low abundance in plant tissues poses a major barrier to large-scale utilization. This review provides a comprehensive and forward-looking synthesis of flavonoid biosynthesis, regulation, transport, and yield enhancement strategies. We highlight key advances in understanding transcriptional and epigenetic control of flavonoid pathways, focusing on the roles of MYB, bHLH, and WD40 transcription factors and chromatin modifications. We also examine flavonoid transport mechanisms at cellular and tissue levels, supported by emerging spatial metabolomics data. Distinct from conventional reviews, this review explores how plant cell factories, genome editing, environmental optimization, and artificial intelligence (AI)-driven metabolic engineering can be integrated to boost flavonoid production. By bridging foundational plant science with synthetic biology and digital tools, this review outlines a novel roadmap for sustainable, high-yield flavonoid production with broad relevance to both research and industry.